2016
DOI: 10.1007/s10068-016-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

A phenyl lipid alkaloid and flavone C-diglucosides from Spergularia marina

Abstract: A phenyl lipid alkaloid and seven phenolic compounds were isolated from the aerial part of , a halophyte that grows on salt marshes and tidal flat. These compounds were identified as 2,4-di--butylphenol, -hexacosanoylanthranilic acid, tryptophan, 4-hydroxybenzyol glucopyranoside, luteolin 6--β-D-glucopyranoside 8--β-D-(2--feruloyl)glucopyranoside, luteolin 6--β-D-(2--feruloyl)glucopyranoside 8--β-D-glucopyranoside, apigenin 6--β-D-glucopyranoside 8--β-D-(2--feruloyl)glucopyranoside, and apigenin 6--β-D-(2--fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In another study [52,53], phenyl lipid alkaloid and several phenolic compounds were identified from S. marina. These compounds were identified as 2,4-di-tert-butylphenol, N-hexacosanoylanthranilic acid, tryptophan, 4 hydroxybenzyol glucopyranoside, luteolin The identified compounds can partially contribute to the antioxidant activity of S. marina.…”
Section: Variation In Phenolic Compounds Content Antioxidant Antimicr...mentioning
confidence: 99%
“…In another study [52,53], phenyl lipid alkaloid and several phenolic compounds were identified from S. marina. These compounds were identified as 2,4-di-tert-butylphenol, N-hexacosanoylanthranilic acid, tryptophan, 4 hydroxybenzyol glucopyranoside, luteolin The identified compounds can partially contribute to the antioxidant activity of S. marina.…”
Section: Variation In Phenolic Compounds Content Antioxidant Antimicr...mentioning
confidence: 99%
“…The remaining 3 protons were detected in the aromatic down eld region between 6.62 and 7.22 ppm, suggesting a tri-substituted aromatic compound. The data were further supported by 13 C NMR (Fig. S2).…”
Section: Qq Bacteria Strain and Qsimentioning
confidence: 56%
“…As previously described (Cho et al 2016), nuclear magnetic resonance (NMR, Bruker Biospin, Fällanden, Switzerland) analysis was carried out after reconstitution of the bioactive fraction in deuterated methanol (CD 3 OD, Cambridge Isotope Laboratories, Inc), containing tetramethyl silane (TMS) as analytical solvents. NMR spectra were recorded on a Bruker Avance III spectrometer (Bruker Biospin) (500 and 126…”
Section: Extraction and Identi Cation Of Qsimentioning
confidence: 99%
See 2 more Smart Citations